The bee fauna of an Atlantic coastal plain tidal marsh community in Southern New England, USA - Zarrillo, Tracy A.; Stoner, Kimberly A. (Journal of Melittology, 2019)
With growing evidence of changes in local abundance, geographical range, and species diversity of wild bees, it is imperative to document wild bee communities in representative habitats throughout North America. The Connecticut shoreline has historically been subject to many natural and anthropogenic disturbances, and there is a lack of baseline data regarding bee biodiversity in Connecticut’s maritime habitats. In this study, we characterize the wild bee fauna of a discrete maritime habitat in Connecticut, USA, and examine salt-marsh, beach dune, and coastal scrub bee communities adjacent to Long Island Sound. Patterns found are discussed in relation to recent coastal surveys in New England. Biweekly surveys were conducted at Grass Island (Guilford, CT) over a two-year period (2011-2012) using pan traps and effort-based (timed) net collecting from flowers. A total of 3928 individual bees were collected, representing five families, 18 genera and at least 80 species. Floral records for 374 individuals resulted in associations of 35 bee species with 19 species of flowers. Seventy percent of the bees captured in the net survey were visiting alien plants, with the exotic Rosa rugosa Thunb. having the highest level of bee diversity and relative abundance. The total number of bee species collected in this survey represents approximately 23% of the known Connecticut fauna, including four specialists associated with coastal and wetland habitats. The abundance and diversity of bees visiting alien plants on Grass Island, as well as the occurrence of these sand specialists, may prove to be of conservation concern as the Connecticut shoreline continues to be altered.